In search of influence of stratospheric Quasi‐Biennial Oscillation on tropical cyclones tracks over the Bay of Bengal region. (13th April 2013) - Fadnavis, S.; Ernest Raj, P.; Buchunde, Pallavi; Goswami, B. N.
ABSTRACT The ability of the stratospheric Quasi‐Biennial Oscillation (QBO) to modulate tropospheric circulation allows it to modulate tracks of tropical cyclones (TCs). This possibility is examined using data on the cyclone tracks over the Bay of Bengal (BOB) during the period 1948–2010. TC tracks (excluding the El Niño‐Southern Oscillation years) when stratified as per the phases of QBO show the evidence of influence of stratospheric QBO on tracks. In pre‐monsoon and post‐monsoon seasons, during easterly phase of QBO, cyclones move westward/northwestward while during westerly phase they move northward/northeastward. The evidence of influence of QBO on modulation of TC tracks is reported for the first time during pre‐satellite period (1948–1978) and satellite period (1979–2010) over the BOB. The QBO influence is observed to be significantly stronger during easterly phase as compared to that in the westerly phase. Numbers of cyclones are more during easterly phase (during pre‐monsoon and post‐monsoon) than during the westerly phase. A mechanism is proposed whereby QBO of the zonal winds in the stratosphere influences the movement of cyclone tracks in the BOB by redistributing deep convection associated with cyclones by modulating steering winds. The possible interaction between QBO and cyclone activity is investigated through the variation of tropopause height, geo‐potential height and Outgoing Longwave Radiations. © 2013 Royal Meteorological Society